2015
DOI: 10.3389/fncir.2014.00148
|View full text |Cite
|
Sign up to set email alerts
|

Changes in functional properties and 5-HT modulation above and below a spinal transection in lamprey

Abstract: In addition to the disruption of neural function below spinal cord injuries (SCI), there also can be changes in neuronal properties above and below the lesion site. The relevance of these changes is generally unclear, but they must be understood if we are to provide rational interventions. Pharmacological approaches to improving locomotor function have been studied extensively, but it is still unclear what constitutes an optimal approach. Here, we have used the lamprey to compare the modulatory effects of 5-HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 82 publications
2
38
0
Order By: Relevance
“…Our study provides an accessible model system to decipher the molecular mechanisms underlying glutamatergic spinal circuit remodelling and regeneration and how these processes could be optimized for therapeutic interventions in mammals. Further, this work stresses the importance of studying the changes above the injury and not only below, as suggested before by other authors47 and also the necessity of increasing our understanding of the spinal circuits not only in lesioned but also in un-lesioned animals4849.…”
Section: Discussionsupporting
confidence: 64%
“…Our study provides an accessible model system to decipher the molecular mechanisms underlying glutamatergic spinal circuit remodelling and regeneration and how these processes could be optimized for therapeutic interventions in mammals. Further, this work stresses the importance of studying the changes above the injury and not only below, as suggested before by other authors47 and also the necessity of increasing our understanding of the spinal circuits not only in lesioned but also in un-lesioned animals4849.…”
Section: Discussionsupporting
confidence: 64%
“…Data is presented as a boxplot to indicate the variability. Data from Cooke and Parker (2009) and Becker and Parker (2015) . No permission is required to reproduce this material.…”
Section: Below Lesion Cellular Changesmentioning
confidence: 99%
“…The mechanism underlying this effect is unknown. It does not seem to reflect an L-type calcium, persistent sodium, or NMDA conductance (see Li et al, 2004a ), increased EPSP summation due to changes in half-width, or the recruitment of polysynaptic inputs ( Cooke and Parker, 2009 ; Becker and Parker, 2015 ). One possibility is that it reflects “synaptic drag” ( Martin and Pilar, 1964 ), an increase in asynchronous vesicle release that can cause slowly developing depolarizations with repetitive stimulation ( Hjelmstad, 2005 ; Iremonger and Bains, 2007 ).…”
Section: Below Lesion Cellular Changesmentioning
confidence: 99%
“…This indicates that serotonin could also be a target of interest in nonregenerating mammalian models of SCI since it can modulate several aspects of the regenerative process. Even more importantly the effects of serotonin revealed in these studies should be taken into account by those authors performing pharmacological treatments with serotonergic drugs to modulate spinal cord circuits and aiming to promote locomotor recovery after SCI (see 46 ), mainly because these treatments could be affecting the regeneration of new neurons or the re-growth of axotomized axons as shown here.…”
Section: Discussionmentioning
confidence: 98%
“…We assumed that these drugs also crossed the blood brain barrier in lampreys as in mammals, since the blood brain barrier of lampreys is similar to that of higher vertebrates 48,49 . Serotonin was applied at the same concentration previously used by other authors 46 . Becker and Parker 46 already reported that this concentration of serotonin affects the swimming behaviour of lesioned and unlesioned animals indicating that this application route also allows access to the CNS.…”
Section: Drug Treatmentsmentioning
confidence: 99%